2012
DOI: 10.1155/2012/235015
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Ownership and Utilization of Insecticide-Treated Bed Nets for Malaria Control in Eastern Ethiopia

Abstract: Background. Malaria remains a major cause of mortality and morbidity in the world, and particularly in sub-Saharan Africa. Objectives. The aim of this study was to determine ownership and utilization of ITNs among households with children under five in the previous night. Methods. A community based cross-sectional study was conducted in Gursum district in Eastern Ethiopia. A total of 335 households were surveyed using a pretested structured questionnaire administered though house-to-house interviews. Results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
47
7

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 26 publications
14
47
7
Order By: Relevance
“…This is consistent with findings from Ethiopia and Kenya (10, 17). In contrary from Ethiopian and Kenyan study evidences, a study conducted at Burkina Faso showed that family size showed no significant difference in under five ITNs utilization (22).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with findings from Ethiopia and Kenya (10, 17). In contrary from Ethiopian and Kenyan study evidences, a study conducted at Burkina Faso showed that family size showed no significant difference in under five ITNs utilization (22).…”
Section: Discussionsupporting
confidence: 93%
“…According to this report, ITNs ownership and utilization of under-5 years old children in Southern, Nation, Nationalities and Peoples Region (SNNPR) of Ethiopia was 57 and 42%, respectively (4). According to studies conducted in different areas of Ethiopia, household ownership of at least one ITNs and ITNs utilization among under-5 years old children were 25.3 and 63.9%, respectively, at Adami Tulu district of Oromia region (9), 62.4 and 21.5%, respectively, at Gursum district of Oromia region (10), 95.8 and 59.1%, respectively, in Dejen Woreda, Amhara region (11), 98.4 and 69%, respectively, in Arbaminch Zuria woreda of SNNPR (6), 44.96 and 32% respectively, Shebedino district, SNNPR (12), 71.64% of utilization, Raya Alamata District of Amhara region (13), ownership was 56.6% in Gilgel-Gibe, Ethiopia (14), in SNNPR, 67.5% of households had used a bed net during the previous night. But, only 9.4% were used by children alone (15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In areas where ownership of ITNs has been enhanced, factors such as area of residence, knowledge on malaria transmission, presence of fever in a child, age, gender and occupational status of the household head and the household size were identified as significant determinants of use of ITNs ( [14]. For instance, a study in Ethiopia [14] found a unit increase in the size of household increased the odds of ownership of a net more than twice. The study further showed that households which had at least one child below five years, the odds of owning any net was about 60% higher than those with no children below five years.…”
Section: Reviewed Literaturementioning
confidence: 99%
“…Studies have identified the factors influencing the ownership and utilisation of longlasting insecticide nets (LLINs) [1][2][3][4][5][6][7][8][9] in and out of Cameroon. The utilisation rate of LLINs, especially amongst children less than five years old and pregnant women are widely low [2,3,10].…”
Section: Introductionmentioning
confidence: 99%